Effect of hand postures and object properties on forearm muscle activities using surface electromyography - Lee, Kyung Sun; Jung, Myung Chul (International Journal of Occupational Safety and Ergonomics, 2020)
Introduction. The objective of this study was to measure the effect of hand postures and object properties on nine forearm muscle activities and their contribution using surface electromyography. Methods. Ten male university students participated in the experiment. The objects used were cylindrical and rectangular, with lengths and weights of 2, 4, 6 and 8 cm and 400, 800, 1400 and 1800 g. The experimenter told the participant to pick up the object using a particular hand posture, lift the object to approximately shoulder height and maintain this posture for 3 s. Results. The hand posture, object size and object weight greatly influenced the muscle activities, but the object shape did not. Pinching with two or three fingers yielded the greatest muscle activities with the 8-cm, 1800-g object. The extensor pollicis longus and flexor pollicis longus muscles exhibited the highest submaximal voluntary contraction. Conclusion. This study provides basic information about the specific activities of the forearm muscles and the effects of the hand postures and object properties on those activities.
Keywords: Adult; Electromyography; Forearm; Hand; Humans; Male; Muscle Contraction; Muscle, Skeletal; Posture; Task Performance and Analysis; Young Adult; contribution; grasping; percentage of maximal voluntary contraction; pinching; surface electromyography